Analisis Kemampuan Berpikir Aljabar Ditinjau dari Gaya Kognitif Siswa - Adilawati, Fitria Legi; Atiqoh, Khamida Siti Nur; Musyrifah, Eva (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
The low ability of algebraic thinking in solving math problems is still a problem. One of the causes is that many students still make mistakes when solving math problems. This study aims to describe the algebraic thinking ability of high school students, cognitive style of Field Independent (FI) and Field Dependent (FD) students, determine the relationship and the magnitude of the influence between algebraic thinking ability with cognitive style of students. This research was conducted at 38 Senior High School  Jakarta, 66 Senior High School Jakarta, and 97 Senior High School Jakarta in the 2023/2024 school year. This research is a quantitative descriptive research, the test instrument is 6 items of description of algebraic thinking ability and GEFT test instrument developed by Witkin. The results showed that students' algebraic thinking ability was in the moderate category. Of the 102 respondents, 59% of students have FI cognitive style about 41% of students have FD cognitive style. There is a significant difference that students with FI cognitive style better than students with FD cognitive style. There is an influence between the cognitive style of students on the ability to think algebraically by 16.70%.